Invasiveness modulation of glioma cells by copper complex-loaded nanoarchitectures - Zamborlin, Agata; Pagliari, Francesca; Ermini, Maria Laura; Frusca, Valentina; Garcia-Calderón, Daniel; Tirinato, Luca; Volante, Stefania; Bresciani, Giulio; Marchetti, Fabio; Seco, Joao; Voliani, Valerio (Colloids and surfaces. B, Biointerfaces, 2025)
Among the tumors with the highest lethality, gliomas are primary brain tumors associated with common recurrence inclined to metastasize along the neuraxis and occasionally out of the central nervous system. Even though metastasis is the main responsible for death in oncological patients, few dedicated treatments are approved. Therefore, the establishment of effective anti-metastasis agents is the final frontier in cancer research. Interestingly, some copper complexes have demonstrated promising efficacy as antimetastatic agents, but they may cause off-site effects such as the alteration of copper homeostasis in healthy tissues. Thus, the incorporation of copper-based antimetastatic agents in rationally designed nano-architectures can increase the treatment localization reducing the side effects. Here, copper complex loaded hybrid nano-architectures (CuLNAs) are presented and employed to assess the impact of an intracellular copper source on glioma cell invasiveness. The novel CuLNAs are fully characterized and exploited for cell migration modulation in a glioma cell line. The results demonstrate that CuLNAs significantly reduce cell migration without impairing cell proliferation compared to standard gold and copper NAs. A concomitant antimigratory-like regulation of the epithelial-to-mesenchymal transition genes confirmed these results, as the gene encoding for the epithelial protein E-cadherin was upregulated and the other explored mesenchymal genes were downregulated. These findings, together with the intrinsic behaviors of NAs, demonstrate that the inclusion of metal complexes in the nano-architectures is a promising approach for the composition of a family of agents with antimetastatic activity.